Community Participation in The Village RKP Planning Process: Case Study of Pao-Pao Village Tanete Rilau Sub-District - Misnawati; Rahmatia; Fatmawati (PT. Maju Malaqbi Makkarana, 2023)
The village is the government that communicates directly with the community and is the center of government development. As such, the village government is an important part of the administration, and the village can have the power to regulate and manage the interests of the community. To achieve community participation, the government has established a forum to implement development plans, namely Muslembang. If community participation is an element of the village development process, community participation has a significant impact on decision-making. The purpose of this study is to obtain an explanatory overview of community participation in the village RKP planning process in Paopao Village, Tanete Lilau District, and to clarify what are the factors that support and hinder community participation in the village RKP planning process. to clarify. Baloo's regent. The type of research used by researchers is qualitative. The location of this survey is in Paopao Village, Tanete Lilau District, Bal Regency. The data collection process used by researchers includes data collection, data reduction, data presentation, and drawing conclusions. The results showed that: In 2019 and 2020, community participation in the village RKP planning process in Paopao Village, Tanete Lilau District, Baru Regency, only village officials participated in the RKP design team, community empowerment executives and community members. elements were not involved. And when it comes to female participation, only one woman reaches up to 30%. Therefore, we cannot speak of participatory advice on development planning. The driving force behind community participation in her RCP planning process for her village in Paopao Village, Tanete Lilau District, Balu District, is the community's awareness of progress in village development as a form of community awareness itself. Encouragement. Prioritize. The barrier to community participation is the individual community itself. Lack of curiosity, economic factors, and the level of education in the community are also among the barriers to participating in the development surprises of Baru Regency, Tanete Lilau District and Paopao Village.